2021
DOI: 10.1590/1517-8692202127012020_0090
|View full text |Cite
|
Sign up to set email alerts
|

Dilemma and Path Selection of College Sports Resources Into the Public Service System of National Fitness in the New Era

Abstract: With the improvement of people's yearning for a healthy and beautiful life, national fitness has become a hot word in academic circles. Combining Data Envelopment Analysis (DEA) and the Tobit technology, this paper constructs the evaluation model of college sports resource efficiency based on the DEA Tobit model. Based on the establishment of the input-output index system of college sports resources, the model achieves the effect of accurate analysis on the allocation efficiency of university sports resources.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…From equation (10) it can be seen that the differential of the probability of choosing a strategy (or the proportion of individuals) within the population is proportional to the value of that probability and the difference between the expected payment for choosing that strategy and the average anticipated payment of the population at this point. Thus, when the right-hand side of the equation is equal to 0, it means that the proportion of strategy s in the population remains unchanged and will become a spontaneous ESS formed by the system after a long period of evolution.…”
Section: ) Evolutionarily Stable Strategies and Evolutionarily Stable...mentioning
confidence: 99%
See 1 more Smart Citation
“…From equation (10) it can be seen that the differential of the probability of choosing a strategy (or the proportion of individuals) within the population is proportional to the value of that probability and the difference between the expected payment for choosing that strategy and the average anticipated payment of the population at this point. Thus, when the right-hand side of the equation is equal to 0, it means that the proportion of strategy s in the population remains unchanged and will become a spontaneous ESS formed by the system after a long period of evolution.…”
Section: ) Evolutionarily Stable Strategies and Evolutionarily Stable...mentioning
confidence: 99%
“…Literature [10] has accurately analyzed the evaluation model of sports resources efficiency in colleges and universities, and the results show that urban colleges and universities have the problems of excessive input of sports resources and low output rate of sports resources. Therefore, urban colleges and universities should make full use of the existing resources to enhance their social sports instructing power and, at the same time, improve the publicity of national fitness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Liu, Z. summarized that national fitness had become popular by recommending buzzwords through big data. Based on the DEA-Tobit model, an evaluation model for the efficiency of sports resource allocation in colleges and universities was constructed, and then 10 colleges and universities were used as experimental objects to test the model and the results showed that the three efficiency indexes in two of them were all 1, and there was the phenomenon of over-investment of sports resources in colleges and universities [17]. Tan, X. et al used a linear programming model to optimize the allocation of community sports facilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e research results show that the development of the sports industry will promote the development of the economy, which in turn promotes the construction of public sports facilities, and the pull rate reaches 1.056%. Liu et al [26] have found that national fitness has become a hot direction. ey used the data envelopment analysis method DEA and Tobit technology to establish a university evaluation model.…”
Section: Related Workmentioning
confidence: 99%